Scattered Bones. - Usman Awang. (Institut Terjemahan & Buku Malaysia Berhad, 2009)
Part of this book is autobiographical while the other part relates the author’s experience as a policeman. Set in Malaya during the Emergency after World War II, it protrays the hardships of people resulting from the devastating war, and the conflict between the British colonists and the Malayan communists.